2010
DOI: 10.1161/circresaha.109.214346
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of CHIP-Mediated p53 Degradation Protects the Heart From Ischemic Injury

Abstract: Rationale: The number of patients with coronary heart disease, including myocardial infarction, is increasing and novel therapeutic strategy is awaited. Tumor suppressor protein p53 accumulates in the myocardium after myocardial infarction, causes apoptosis of cardiomyocytes, and plays an important role in the progression into heart failure. Objectives: We investigated the molecular mechanisms of p53 accumulation in the heart after myocardial infarction and tested whether anti-p53 approach would be effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 39 publications
8
139
0
Order By: Relevance
“…Furthermore, transfer of these extracellular microRNAs accelerated cell death ( Figure 3). Taken together with our recent finding that p53 accumulation in the myocardium in response to pressure overload or after MI plays an essential role in HF progression in mice, 12,13 our present results suggest that activation of p53 and the increased expression of the p53-responsive microRNAs, miR-192, miR-194, and miR-34a, are likely involved in the pathogenesis of HF after AMI. However, it remains undetermined whether circulating p53-responsive microRNAs were derived from infarct or ischemic heart tissues.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, transfer of these extracellular microRNAs accelerated cell death ( Figure 3). Taken together with our recent finding that p53 accumulation in the myocardium in response to pressure overload or after MI plays an essential role in HF progression in mice, 12,13 our present results suggest that activation of p53 and the increased expression of the p53-responsive microRNAs, miR-192, miR-194, and miR-34a, are likely involved in the pathogenesis of HF after AMI. However, it remains undetermined whether circulating p53-responsive microRNAs were derived from infarct or ischemic heart tissues.…”
Section: Discussionsupporting
confidence: 87%
“…43 In addition, overexpressing CHIP, which induces the degradation of p53, attenuated the accumulation of p53 and reduced cardiomyocyte apoptosis after myocardial infarction. 4 These findings indicate that p53 promotes the deterioration of cardiac function.…”
Section: Roles Of P53 In the Development Of Hfmentioning
confidence: 90%
“…It is recognized as one of the pro-apoptotic genes, and p53 transcriptional activity increased when ischemia and hypoxia (16), mediating apoptosis of p53-dependent myocardial cells (17). In this study, we found that expression level of p53 mRNA enhanced significantly after H/R, which showed p53 have participated in the apoptosis of MMECs caused by H/R.…”
Section: Discussionmentioning
confidence: 51%